2013
DOI: 10.5465/amj.2011.0555
|View full text |Cite
|
Sign up to set email alerts
|

Do They Walk the Talk? Gauging Acquiring CEO and Director Confidence in the Value Creation Potential of Announced Acquisitions

Abstract: We explore whether acquiring CEOs and directors act consistently with the idea that their newly announced acquisitions will increase long-term firm value. Specifically, we examine postannouncement adjustments to CEOs' equity-based holdings and find acquiring CEOs tend to exercise options and sell firm stock following acquisition announcements. Moreover, positive short-term market performance exacerbates this effect. Further, we find directors tend to grant their acquiring CEOs stock options, after acquisition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 114 publications
(145 reference statements)
1
62
0
Order By: Relevance
“…In support, research has shown that acquiring another firm typically increases CEOs' pay much more quickly than does internal or organic growth (Bliss and Rosen, ; Harford and Li, ; Shelton, ). More recently, drawing on Bliss and Rosen's (: 110) argument that “even mergers which reduce shareholder value can be in a manager's private interest,” Devers and colleagues () suggested that personal interests, such as increasing compensation, discretion, and power, may actually provide the motivating forces behind many CEOs' acquisition decisions.…”
Section: Theory Developmentmentioning
confidence: 97%
See 1 more Smart Citation
“…In support, research has shown that acquiring another firm typically increases CEOs' pay much more quickly than does internal or organic growth (Bliss and Rosen, ; Harford and Li, ; Shelton, ). More recently, drawing on Bliss and Rosen's (: 110) argument that “even mergers which reduce shareholder value can be in a manager's private interest,” Devers and colleagues () suggested that personal interests, such as increasing compensation, discretion, and power, may actually provide the motivating forces behind many CEOs' acquisition decisions.…”
Section: Theory Developmentmentioning
confidence: 97%
“…Recent research suggests that these factors are especially salient to underpaid CEOs, as they likely perceive they are undervalued and underappreciated, compared to peers leading similar firms with comparable characteristics and performance (Fong et al ., ; Wade et al ., ). Nevertheless, recent evidence suggests that CEOs who acquire primarily for self‐interested reasons (e.g., increasing subsequent pay) simultaneously perceive increased downside risk related to those acquisitions, and thus engage in actions intended to minimize that risk (Devers et al ., ). Specifically, scholars suggest that, when acquirers are uncertain about the value creation potential of their acquisitions, they tend to finance deals with higher levels of stock, to help offset that risk (Schijven and Hitt, ).…”
Section: Introductionmentioning
confidence: 99%
“…Upper echelons theory suggests that bounded rationality and other cognitive biases play important roles in many strategic decisions (Hambrick, 2007). In the context of mergers and acquisitions, acquiring firm leaders' 55 hubris (Hayward & Hambrick, 1997), narcissism (Chatterjee & Hambrick, 2007) and self-interest (e.g., Deutsch, Keil, & Laamanen, 2007;Gamache, McNamara, Mannor, & Johnson, 2014;Devers, McNamara, Haleblian, & Yoder, 2013) have been shown to influence decisions in the deal-making phase. Leaders' prior experience (e.g., Walters, Kroll, & Wright, 2008;McDonald et al, 2008), functional position (Melone, 1994), gender (e.g., Chen, Crossland, & Huang, 2014), tenure and educational background (Nadolska & Barkema, 2014) also influence decisions regarding whether to acquire a firm and how much to pay.…”
Section: Decision-makingmentioning
confidence: 99%
“…The board thus represents a primary governance mechanism, establishing the compensation schemes described above and monitoring CEO actions (e.g., Devers, McNamara, Haleblian, & Yoder, 2013). Because the CEO sits at the nexus of the board and the firm's management, research about the board's monitoring function typically looks at the CEO's structural position relative to the board and the independence of the board from the CEO (Boyd, 1995;Finkelstein & D'Aveni, 1994).…”
Section: The Board's Monitoring Functionmentioning
confidence: 99%